Literature Review on the Materials, Advantages, and Disadvantages of Suturing Training Tools in Health Education - Nur, Sulistia; Marsim, Etanaulia; Ukhtul Fitri, Riki; Prawibowo, Hartanto (INDOGENIUS, 2025)
Background & Objective: Suturing skills are a fundamental competency in both nursing and medical education. To support the mastery of this skill, effective, realistic, and pedagogically appropriate training tools are essential. Various materials have been employed to create suture training models; however, no single material has emerged as universally ideal or standardized globally. Aims: This review aims to identify the types of materials used in suturing training tools, evaluate their strengths and limitations, and assess their contribution to the global development of simulation-based training devices. Method: This study is a literature review analyzing five recent and relevant scientific articles. The selection criteria included thematic relevance, publication year, and a focus on evaluating suture training tools or materials. Analysis was conducted using the JBI Critical Appraisal Checklist for Case Reports. This literature review highlights aspects such as material properties, advantages, disadvantages, and implications for educational practice. Result: The review identified five primary categories of materials used in suture training tools: (1) polydimethylsiloxane (PDMS) with silk fibers, (2) silicone pads and polyurethane foam, (3) porcine skin, sponges, and commercial pads, (4) improvised combinations such as citrus fruits and tea towels, and (5) synthetic polyurethane-based skin. Each material offers specific benefits, such as high realism, durability, or affordability. Nevertheless, all materials exhibit limitations, including ethical concerns, hygiene issues, and limited anatomical fidelity. Conclusion: This literature review indicates that no single material fully satisfies all requirements for suturing training. A combined and contextual approach considering learning objectives, cost, and local availability emerges as a pragmatic alternative. The contribution of this review lies in strengthening the global research direction toward the development of accessible, inclusive, and adaptable medical simulation tools tailored to diverse healthcare education settings worldwide.